Effects of Dark Brooder Rearing and Age on Hypothalamic Vasotocin and Feather Corticosterone Levels in Laying Hens - Nordquist, Rebecca E.; Zeinstra, Elisabeth C.; Dougherty, Alyssa; Riber, Anja B. (Frontiers in Veterinary Science, 2020)
Chickens cannot independently thermoregulate at hatch and lack opportunity to behaviorally thermoregulate with a hen in the egg layer industry, thus barns are heated to thermoneutral temperatures. Dark brooders are low-energy-consuming hot plates, which may be environmentally advantageous while providing welfare-enhancing aspects of maternal care (i.e. shelter and separation of active and inactive individuals). Dark brooder use has been demonstrated to decrease injurious pecking and mortality well into the production period of layers. To further understand hen development around lay onset and effects of dark brooders on the brain and HPA-axis, we examined effects of rearing with dark brooders on expression of vasotocin (AVT) in the hypothalamus and corticosterone (CORT) in the feathers of in total 48 layer Isa Warren hens at 16 w and 28 w of age (n=12 per age and treatment). An age-dependent decreased number of AVT-positive neurons was seen in the medial preoptic area, medial preoptic nucleus, paraventricular nucleus, rostral part (prepeduncular hypothalamus), and lateral preoptic area. Trends to effects of brooder rearing were found in both anteromedial preoptic nucleus and supraoptic nucleus, with dark brooder reared animals showing higher mean counts of AVT-positive neurons in both areas. No interactions between brooder raising and age were observed in AVT-positive neuron count. CORT levels were higher in primary wing feathers from 28 week old hens than in those from 16 week hens. No main effects of rearing with dark brooders or interactions between age and treatment were found on CORT levels. The age-dependent effects seen in the hypothalamus and CORT aids in further understanding of the development of chickens around puberty. The use of brooders tended to increase AVT expression in the anteromedial preoptic nucleus and supraoptic nucleus, an indication that dark brooder rearing may affect physiological responses regulated by these areas. The lack of effect of dark brooders on CORT in feathers is at the least an indication that the use of dark brooders is not stressful; in combination with the benefits of dark brooders on injurious pecking, fearfulness and early mortality, this pleads for the use of dark brooders in on-farm situations.